EVALUATION OF DIURETIC ACTIVITY OF ETHANOLIC EXTRACT OF LEAVES OF PIPER BETEL IN ALBINO RATS - YADAV, NISHANT; SINGH, AJEET PAL; SINGH, AMAR PAL (International Journal of Current Pharmaceutical Research, 2026)
Objective: To assess the diuretic capability of the alcoholic extract of Piper betel leaves, the current research was planned to make use of the Lipschitz technique on albino rats. Methods: Four groups of albino rats were used for the experiment, and diuretic activity was assessed in metabolic cages. Group I served as the control and received normal saline (10 ml/kg, p. o. or 1 ml of 0.9% NaCl/100 g). Group II received the standard diuretic drug frusemide (10 mg/kg, p. o). Groups III and IV were treated with the alcoholic extract of Piper betel leaves at doses of 200 mg/kg and 400 mg/kg, respectively. Following drug or extract administration, all animals were hydrated with normal saline (15 ml/kg, p. o.) and placed individually in metabolic cages maintained at 25 °C±0.5 °C. Food and water were withheld during the 5 h study period. At the end of 5 h, urine was collected and analyzed for total volume, pH, and electrolyte content (sodium, potassium, and chloride ions). Results: Compared to the control group, both doses of the Piper betel leaf extract significantly increased urine output and promoted greater excretion of sodium, potassium, and chloride ions. No remarkable differences in urinary pH were observed between the groups. Conclusion: A single administration of frusemide as well as the alcoholic extract of Piper betel leaves enhanced urine production and electrolyte excretion. At the higher dose (400 mg/kg), the extract demonstrated a diuretic effect comparable to that of the standard drug frusemide.